Antibiotic perseverance increases the risk of resistance development - Brandis, Gerrit; Larsson, Jimmy; Elf, Johan (Uppsala University, 2022)
Experimental data description

All experiments performed are timelapse microscopy experiments. Each experiment contains two directories, one containing phase contrast images arranged by positions on the microfluidic device, and the other contains the analysis scripts. The 'Overview.csv' file contains a full description for the conditions in each experiment.

Experiments can be divided into 3 categories:

1. 4h exposure to various antibiotics (E. coli)

These are the main experiments within the paper where cells are exposed to various antibiotics at 1/8x, 1/4x, 1/2x and 1x MIC.

a) EXP-21-BW5663_LB-1.zip (LB replicate 1)

b) EXP-22-BY2422_LB-2.zip (LB replicate 2)

c) EXP-21-BW5667_CAR-1.zip (CAR replicate 1)

d) EXP-22-BY1020_CAR-2.zip (CAR replicate 2)

e) EXP-21-BT2897_CRO-1.zip (CRO replicate 1)

f) EXP-22-BY2425_CRO-2.zip (CRO replicate 2)

g) EXP-21-BY1007_CHL-1.zip (CHL replicate 1)

h) EXP-22-BY1043_CHL-2.zip (CHL replicate 2)

i) EXP-21-BT2896_CIP-1.zip (CIP replicate 1)

j) EXP-22-BY2424_CIP-2.zip (CIP replicate 2)

k) EXP-21-BW5664_GEN-1.zip (GEN replicate 1)

l) EXP-22-BY1022_GEN-2.zip (GEN replicate 2)

m) EXP-21-BW5666_NIT-1.zip (NIT replicate 1)

n) EXP-22-BY2419_NIT-2.zip (NIT replicate 2)

o) EXP-21-BT2898_RIF-1.zip (RIF replicate 1)

p) EXP-21-BY1000_RIF-2.zip (RIF replicate 2)

q) EXP-21-BW5661_SPT-1.zip (SPT replicate 1)

r) EXP-21-BY1019_SPT-2.zip (SPT replicate 2)

s) EXP-21-BW5658_TET-1.zip (TET replicate 1)

t) EXP-22-BY2421_TET-1.zip (TET replicate 2)

2. 17h exposure to rifampicin (E. coli, S. enterica)

These experiments were performed to test the effect of long-term rifampicin exposure on Escherichia coli and Salmonella enterica.

a) EXP-21-BT2899.zip (E. coli)

b) EXP-21-BY1015.zip (S. enterica)

3. Growth in minimal medium (E. coli)

This experiment was performed to test how reducing the cellular growth rate (without antibiotics) affects the cell-to-cell growth heterogeneity.

a) EXP-22-BY2420.zip

Code

The 'codefolder' contains the ImAnalysis pipeline and the UNet used for image analysis. The scripts and parameter files to perform the image analysis are provided within each individual experiment folder.

The 'Data_analysis' folder contains three directories: (i) 'Analysis_scripts', which contains the R scripts used for data analysis and figure generation; (ii) 'Raw_data', which contains the raw data underlying the figures in the paper; and (iii) 'Results', which is the output directory for the figures generated by the analysis scripts.
Keywords: Bacteriology; Medical and Health Sciences; Medicin och hälsovetenskap; Biological Sciences; Biologi